1991
DOI: 10.1111/j.1527-3466.1991.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Ro 40–5967: A New Nondihydropyridine Calcium Antagonist

Abstract: Key Words: Ro 40-5967--calcium antagonists-hypertension-coronary heart diseaseCalcium antagonists are now widely used for the treatment of angina pectoris and hypertension (for review, see ref. 25). Despite different chemical structures, they all inhibit the slow Ca2+ inward current (7,15). Three main classes of calcium antagonists have been described: dihydropyridines, represented by nifedipine; phenylalkylamines, represented by verapamil; and benzothiazepines, represented by diltiazem. Each of these compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…One measure is to examine the plasma levels of the drug. Cremers et al (1997) suggested that the therapeutic active plasma concentration (TAPC) was 0.14 mM for verapamil and nifedipine, and 0.87 mM for mibefradil (see Henry, 1980;McAllister & Kirsten, 1982;Clozel et al, 1991). If these plasma concentrations are in equilibrium with the vascular and cardiac calcium channels then our studies suggest that verapamil would give 20 ± 30% relaxation of small arteries but more than 70% inhibition of myocardial force, indicating a preferential e ect on myocardium.…”
Section: Human Vascular To Cardiac Selectivitymentioning
confidence: 91%
See 1 more Smart Citation
“…One measure is to examine the plasma levels of the drug. Cremers et al (1997) suggested that the therapeutic active plasma concentration (TAPC) was 0.14 mM for verapamil and nifedipine, and 0.87 mM for mibefradil (see Henry, 1980;McAllister & Kirsten, 1982;Clozel et al, 1991). If these plasma concentrations are in equilibrium with the vascular and cardiac calcium channels then our studies suggest that verapamil would give 20 ± 30% relaxation of small arteries but more than 70% inhibition of myocardial force, indicating a preferential e ect on myocardium.…”
Section: Human Vascular To Cardiac Selectivitymentioning
confidence: 91%
“…In assay screens, it showed a selective coronary vasodilating property in Langendor perfused guinea pig isolated heart at 12 fold lower concentrations than required to depress left ventricular pressure. This vascular selectivity was absent for verapamil (Clozel et al, 1991;BuÈ hler et al, 1997). Subsequently, Mishra & Hermsmeyer (1994) showed that in voltage clamp studies in single cells from rat azygos vein, mibefradil had 30 ± 100 times greater potency at halving the barium current for transient T-type calcium channels than for the long opening higher conductance L-type channels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of the present study was to examine which types of calcium channels are functionally important in the sympathetic nerve terminals of human cardiac tissue. This question was also addressed in the context of the possibility that the favorable bradycardic influence of the novel calcium channel blocker mibefradil 4,5 might be due to an inhibition of norepinephrine release by inhibiting calcium influx into the cardiac sympathetic nerve terminals. 6 The purpose of the present experiments with mibefradil was to provide evidence for the suggestion that mibefradil inhibits norepinephrine release by blocking calcium channels in the postganglionic sympathetic axon terminals.…”
mentioning
confidence: 99%
“…, Clozel et al, 1991) compared to diltiazem (0.19 mmol l 71 , Henry, 1980) used because of the lack of negative inotropic eect at these concentrations. In addition, it has been shown that chronic treatment with mibefradil potentiated the endothelium-dependent relaxation in the aorta of hypertensive salt sensitive Dahl rats (Boulanger et al, 1994).…”
mentioning
confidence: 99%
“…-channel antagonists in the treatment of heart failure patients. TAPC: therapeutic active plasma concentration (diltiazem, nifedipine: Henry (1980); mibefradil: Clozel et al (1991)), IC 25 : drug concentration required to decrease the developed force of contraction by 25% of the basal force of contraction in multicellular muscle strips as well as in isolated coronary artery rings, PAP: isolated, electrically driven, left ventricular muscle strip, CAR: coronary artery rings.…”
mentioning
confidence: 99%